ASPM Promotes the Progression of Anaplastic Thyroid Carcinomas by Regulating the Wnt/β-Catenin Signaling Pathway - Liang Jiang; Shuai Zhang; Ning An; Guoqing Chai; Changhong Ye (International Journal of Endocrinology)
Background. Abnormal spindle-like microcephaly-associated protein (ASPM) is closely correlated with several malignant tumors, whereas little is known about the role of ASPM in anaplastic thyroid cancer (ATC). Herein, we sought to investigate whether ASPM is involved in the pathogenesis of ATC and the underlying mechanisms. Methods. The data from two data sets (GSE76039 and GSE33630) were extracted and analyzed for the expression of ASPM, followed by a further validation in collected ATC patients using quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting. The effect of ASPM on cell proliferation, migration, invasion, and cell cycle was explored in ATC cell lines by in vitro inhibition of ASPM, while ASPM-mediated tumorigenicity was investigated in a xenograft tumor model. The involvement of Wnt/β-catenin signaling pathway was also investigated. Results. ASPM was overexpressed in ATC patients and cell lines. In vitro knockdown of ASPM inhibited the proliferation, migration, and invasion capabilities of ATC cells and induced cell cycle arrest. Wnt/β-catenin signaling was suppressed in response to ASPM inhibition, while rescue of β-catenin expression restored the impaired biological functions of ATC cells. In vivo transplantation of ASPM-knockdown cells inhibited the growth of tumors. Conclusions. Upregulation of ASPM promotes the malignant properties of ATC cells and contributes to tumorigenesis through the Wnt/β-catenin signaling pathway.